2022
DOI: 10.14814/phy2.15112
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and cardiac autonomic adaptations to isometric exercise training: A randomized sham‐controlled study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 37 publications
(56 reference statements)
2
29
0
1
Order By: Relevance
“…This study echoes the wider mechanistic literature in that IET predominantly induces reductions in resting BP independent of changes in CO [1,7,8]. Although significant reductions are seen in resting HR, CO remains unchanged as the consequence of a significant increase in SV, which is likely mediated through the significant left ventricular functional and mechanical adaptations recently reported following IET [30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study echoes the wider mechanistic literature in that IET predominantly induces reductions in resting BP independent of changes in CO [1,7,8]. Although significant reductions are seen in resting HR, CO remains unchanged as the consequence of a significant increase in SV, which is likely mediated through the significant left ventricular functional and mechanical adaptations recently reported following IET [30].…”
Section: Discussionsupporting
confidence: 81%
“…Using the Bend and Squat device, the home-based wall squat protocol involved participants resting their back against a fixed wall with their feet placed parallel and shoulder width apart, while their arms remained relaxed down by their side (see Supplement File for further details, http://links.lww.com/HJH/C53). Each session involved of 4 x 2-min bouts of isometric wall squat, separated with 2-min rest intervals, with at least 48-h recovery between every session [7–9]. To allow for close monitoring of intensity and adherence, all participants recorded HR and rate of perceived exertion data following each IET bout and uploaded their data to a personal online database, which was monitored by the investigators.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, the greater attention/contact that the intervention groups received may also have contributed to the beneficial trends of IRT, although a previous study which compared wall squat with a sham wall squat (inadequate intensity) only demonstrated BP reductions in the “true” intervention group suggesting that the effects are specific to the exercise itself. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the greater attention/contact that the intervention groups received may also have contributed to the beneficial trends of IRT, although a previous study which compared wall squat with a sham wall squat (inadequate intensity) only demonstrated BP reductions in the "true" intervention group suggesting that the effects are specific to the exercise itself. 26 While we did not evaluate physiological parameters which might explain the SBP reductions observed, a recent meta-analysis concluded that the principal driver of IRT induced BP reduction is reduced total peripheral resistance, potentially mediated through enhanced autonomic vasomotor control. Changes in cardiovascular function including significantly decreased heart rate and increased stroke volume (with stable cardiac output) are also consistently reported.…”
Section: Blood Pressure Changes-phasementioning
confidence: 97%
“…Isometric exercise training (IET) is a highly effective and time‐efficient anti‐hypertensive intervention, with multiple meta‐analyses demonstrating statistically and clinically significant reductions in resting blood pressure (BP) (Edwards et al, 2022; Inder et al, 2016; López‐Valenciano et al, 2019). Fundamentally, these BP reductions have been largely attributed to changes in peripheral vascular resistance, rather than adjustments to central cardiac output (de Caux et al, 2021; Taylor et al, 2019). Despite this, the effects of IET on parameters of arterial stiffness remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%